World First for Diamond in Synchrotron-Based IR Photothermal Nanospectroscopy. Issue 4 (3rd July 2016) - Cinque, Gianfelice; Kelley, Chris S.; Frogley, Mark D.; Filik, Jacob; Wehbe, Katia; Fitzpatrick, Ann; Donaldson, Paul M.
Abstract : For the first time, infrared spectra on the sub-wavelength scale have been delivered by a synchrotron-radiation-induced thermal expansion technique [1 ]. The novel experimental result was achieved by coupling an atomic force microscope (AFM) to an infrared (IR) beamline at the UK's national synchrotron facility, Diamond Light Source. Via broadband synchrotron illumination and an AFM sub-micron tip, molecular IR spectra were obtained by detecting a resonance-enhanced (RE) photothermal signal with spatial resolution beyond the diffraction limit. Together with results on synchrotron IR nanoscopy in scattering mode from the IR beamline at the Advanced Light Source two years ago, the Diamond photothermal nanoprobe approach moves vibrational analysis beyond the diffraction limit and into nanoscale absorption spectroscopy.